Rethinking Digital Games in a Critical and Participatory Perspectives. A Brief Reflection - da Silva Leite, Patrícia; Andrade Torquato Schimidt, Deborah (ETHICS IN PROGRESS, 2019)
Digital games are social objects created based on our culture and society and at the same time they contribute to shaping our world. Through a critical perspective of digital games and technology, it is possible to discuss the unfolding of these artefacts in our society and also understand their relevance beyond an instrumental view. In this paper, we present a brief reflection based on two researches developed by the authors: the first, regarding the link between digital games and people with disabilities; and the second, about contributions of digital games to a critical education. Our goal with this work is to highlight the emancipatory and participatory potential present in the critical vision of digital games.